The effect of semen cuscutae flavonoid on Sertoli cells and blood-testis barrier in male infertility: integrating network pharmacology and experimental verification - Chen-xiao Liu; Su-qin Hu; Dian-long Liu; Ya-hui Xu; Ke Hu; Jian Guo (Taylor & Francis Group, 2023)
AbstractContext Semen cuscutae is commonly used to treat male infertility (MI), and semen cuscutae flavonoid (SCF) is the main active component of semen cuscutae. The therapeutic mechanism of SCF on MI is still unclear.Objective To clarify the mechanisms of SCF against MI.Materials and methods Network pharmacology and molecular docking were used to predict the potential pathways of SCF against MI. Primary Sertoli cells (SCs) were extracted from testis of 60-day-old rats and divided into Control, Model, and 3 treatment groups. The Control and Model groups were given normal medium, the treatment groups were treated with various concentrations of SCF-containing medium (200, 400, and 800 μg/mL). After 24 h, the Model and treatment groups were exposed to heat stress at 43 °C for 15 min. Western blotting and immunohistochemistry were used to detect the expression of targets.Result Network pharmacology indicated that the treatment of SCF on MI was closely related to PI3K-AKT signaling pathway. The in vitro experiments showed that SCF could up-regulated the expression of AKT, AR, occludin, and Ki67, and down-regulated the expression of CK-18 in SCs after heat stress. The AKT inhibitor could block this process.Conclusions SCF can treat MI by regulating the proliferation and differentiation of SCs and the integrity of the blood-testis barrier. The study could provide experimental basis for clinical research.